Ressonâncias entre o Expressionismo abstrato e o Free Jazz - Amorim, Gabriel Rossetto (2024)
We investigated parallels between music and painting in the 20th century, with a particular focus on the programs of abstract expressionism and free jazz, in the 1950s and 1960s. The primary objective was to identify similarities between these two distinct types of artistic expression. To achieve this objective, we adopted a methodological approach based on the concept of “resonances”, conceived by Freitas (2012), according to which the observer brings together artistic works from different modalities with the aim of extracting new readings and interpretative layers. With the approximations between musical and pictorial materials/techniques, we investigate possible similarities nurtured from our artistic experience, from a phenomenological perspective. The subsequent discussion highlighted the capacity of interarts approaches to expand the interpretative scope of works, often unveiling layers of meaning that were supported by the relationship between the medium and experience (MCLUHAN, 1964). We believe that the album “Free jazz: a collective improvisation” (1960) by Ornette Coleman and the painting “White light” (1954) by Jackson Pollock acquire similarities mainly in the tactile context and in the importance given to improvisation, as the driving force of these arts. When we listen to music through phonograms through headphones, we reduce the distance from the sound source to our hearing aid, providing the experience with a heightened sense of tactility, which will be supported by the theory of audiotactile music (CAPORALETTI, 2018). Furthermore, we explore the ambivalences underlying the comparative analysis of these two artistic modalities. We conclude, therefore, that this study promoted updated perspectives in the field of interdisciplinary approaches between music and painting, in the aforementioned section, based on analyzes of the poetics of Jackson Pollock inserted in the abstract expressionism movement and recordings by Ornette Coleman and his improvisation group free jazz collective, outlining new paths for convergence between these two creative domains within the scope of the interartistic experience that involves the subject, environment and environment in contemporary times.